Faktor Risiko Keluhan Digital Eye Strain Pada Mahasiswa Karena Peningkatan Penggunaan Perangkat Digital di Masa Pembelajaran Daring - Fea Firdani; Shafina Putri Aliffa; Nizwardi Azkha (HB PRESS, 2023)
Because of the COVID-19 pandemic, learning method is conducted through online learning and the number of students who use digital device is increasing. The purpose of this study was to determine the risk factors of DES in Informatic Engineering student of Polytechnic C. This research used cross-sectional design, was conducted in February-June 2022 on 90 respondents of Informatic Engineering of Polytechnic C students 2018-2021. The data was analyzed using univariate, bivariate, and multivariate methods. The result showed the highest score of DES was 102, lowest score was 5, and average score was 36.26. 54,6% of the respondents were male, 95,6% used digital device for >4 hour, 52,2% did not use glasses when using digital devices, 94,4% not doing eye rest, 76,7% used digital devices in non-ergonomic position, 70,0% used digital devices with risky viewing angle, and 83,3% used digital devices with risky vision distance. There were differences of DES between the duration of digital device usage >4 and ?4 hour (p=0.033), ergonomic and non-ergonomic position (p=0.022) and risky and non-risky angle of digital device usage (p=0.033). There were no differences of DES between gender (p=0.251), using and not using glasses (p=0.932), doing and not doing eye rest (p=0.543), and risky and non-risky vision distance (p=0.426). The position of digital device usage has the most influence on DES (B=-15.521). It is recommended for students when using digital devices to practice ergonomics position.